2016
DOI: 10.1016/j.pharep.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term administration of pantoprazole on bone mineral density in young male rats

Abstract: We observed that PPIs might have a negative impact on bone formation in growing rats mainly due to their inhibitory effects on the gastric proton pump, with probable deterioration of calcium absorption and decrease in growth plate thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The topic remains a matter of debate. A positive, albeit modest, association between PPIs and OP was reported in animal [ 262 , 263 , 264 ] and numerous of human studies. Many studies and meta-analyses suggested that acid inhibitors, especially the PPIs, moderately increase risk of fractures, particularly in older adults (who are already at higher fracture risk); the risk increases with longer durations of PPI use, often only in the presence of at least one other RF for OP such as older age, female gender and a higher comorbidity score [ 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 95%
“…The topic remains a matter of debate. A positive, albeit modest, association between PPIs and OP was reported in animal [ 262 , 263 , 264 ] and numerous of human studies. Many studies and meta-analyses suggested that acid inhibitors, especially the PPIs, moderately increase risk of fractures, particularly in older adults (who are already at higher fracture risk); the risk increases with longer durations of PPI use, often only in the presence of at least one other RF for OP such as older age, female gender and a higher comorbidity score [ 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 95%
“…By contrast, Matuszewska et al (2016) did not detect any changes in bone microstructure of Wistar rats treated with pantoprazole (3 mg/kg for 84 days). 28 Similarly, Veggar et al (2017) did not observe changes in femoral trabecular and cortical structures of mice with impaired mobility and treated with pantoprazole (100 mg/kg bw daily, 3 weeks). However, they reported a marginally higher lumbar Tb.Th in these mice compared with the untreated mice.…”
Section: Discussionmentioning
confidence: 92%
“…Clinical meta-analyses have also shown that PPI use increases the risk of hip, spine, or vertebral fracture (Ito and Jensen 2010 ; Yu et al 2011 ; van der Hoorn et al 2015 ; Chen et al 2016 ; Poly et al 2018 ), and patients treated with PPIs for two years are more likely to have a hip fracture (OR = 1.30, CI = 1.21–1.39) (Corley et al 2010 ). In addition, animal experiments showed that pantoprazole treatment for 12 weeks had a negative effect on bone metabolism in young male rats (Matuszewska et al 2016 ), and pantoprazole (100 mg/kg/day) could affect fracture healing in mice (Histing et al 2012 ; Menger et al 2020 ). However, there have been few studies on the molecular mechanism of the effect of PPIs on osteocytes in vitro.…”
Section: Introductionmentioning
confidence: 99%